Developmental assessment and early intervention for children with developmental delays: A case study in South Australia - Mardiyanti, Mardiyanti; Case, Amanda (Belitung Nursing Journal, 2021)
Background: Child development monitoring and screening have been mandated as a national health service worldwide, including Indonesia; however, a recent study found that Indonesian community health nurses experienced difficulties detecting and stimulating a child suspected of a developmental delay. Objective: To explore and provide an example of how Australian community health nurses, along with other professionals, contribute to a Universal child and family health service (UCFHS), a similar programme name in Indonesia is child developmental stimulating, detecting monitoring and early intervention programme or SDIDTK. Case study: This is a case study of a young Australian boy (4 years old) whom the mother reported that her son has unclear speech and he was not speaking as much as other children at his age. The researcher, as a nurse, delivered the child developmental assessment and play skills assessment and found that the child has subtle developmental gaps and was at risk for developmental delay. Several goal setting and programming ideas have been developed to meet the child developmental milestones. These include goals in fine motor skills, communication, problem-solving and personal-social skills which have been regarded as early intervention for the child. Together with the therapy from a Speech Pathologist, these goal settings and programming ideas have been collaborated with the kindergarten teachers and the family as well as the UCFHS nurses as part of the child developmental monitoring programme. Conclusion: Developmental delays can be detected through developmental and play assessments and can be followed by developmental stimulation and early intervention programme by developing goal settings and programming ideas around the delays or gaps in play or development.